PENGARUH KOMPENSASI, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus UD. Darma Cipta Karya Lasem) - Nurhidayati, Anik; Baha’udin, Misbah (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTThis study aims to prove the effect of compensation, competence and work discipline on job satisfaction of UD employees. Darma Cipta Karya Lasem both partially and together. The formulation of the problem in this study is how the influence of compensation, competence, and work discipline on job satisfaction of UD employees. Darma Cipta Karya Lasem. Data collection techniques in this study were questionnaires. The test instruments used by researchers are the reliability and validity tests. This study takes a population of employees of UD. Darma Cipta Karya Lasem, totaling 127 people. The data analysis technique used in this study uses multiple linear regression analysis.The results of the study showed that compensation had no significant negative effect on employee job satisfaction, competence had no significant positive effect on employee job satisfaction and work discipline had a significant positive effect on employee job satisfaction. Simultaneous test results show that compensation, competence, and work discipline simultaneously have a significant positive effect. Determination test results showed a value of 0.163 which means that the compensation, competency, and work discipline variables were able to explain the job satisfaction variable by 16.3%. The remaining 83.7% is influenced by other factors outside the research model.Keywords: Compensation, Competence, Work Discipline, Job Satisfaction